THE MIDDLE EAST CRISIS AND POLITICAL SOLUTIONS: IMPLICATIONS OF THE USA–ISRAEL–IRAN/IRAQ CONFLICT ON NIGERIA’S SOCIOECONOMIC STABILITY - Sani Kasimu; Abubakar Lawan; Mercy Pajo; Okaula, Inalegwu Okoh (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: The ongoing conflict involving the United States, Israel, Iran, and Iraq has significant geopolitical and economic ramifications, extending far beyond the Middle East to countries such as Nigeria. Method: This study examines both the political solutions proposed to mitigate the crisis including ceasefire and diplomatic mediation, inclusive regional negotiations, confidence-building measures, strengthening Iraqi governance, and long-term peace frameworks and the socioeconomic impact on Nigeria, particularly in terms of energy prices, inflation, foreign exchange stability, and household welfare. Results: Drawing on verified international and local sources, the research underscores that the resolution of the Middle East conflict through political and diplomatic measures is critical not only for regional stability but also for protecting Nigeria’s economy and social well-being. Novelty: The findings suggest that Nigerian policymakers must consider both global dynamics and domestic resilience strategies to buffer citizens from indirect consequences of international crises.